The Combustion Behavior and Emission of the Carbonized Biomass-Lignite Blended Briquettes - Lukas Kano Mangalla; Mustarum Musaruddin; Agustinus Lolok (Dinamika : Jurnal Ilmiah Teknik Mesin, 2016)
The biomass briquette is an alternative energy resource for the home industries as well as the power generations in many countries. In this study, the combustion behavior and emission characteristic of bio-briquettes from carbonized biomass (e.q.; Rice-hull and teak wood) and lignite coal blended are comprehensively investigated. The biomass used in this study consists of 50% rice husk and 50% teakwood. The biomass (B) and lignite (C) were mixed together with a composition of 50% C/B, 70% C/B and 100% C/B respectively. All compositions were added with 30% binder from cassava. Each composition was selected 3 grams, 4 grams and 5 grams to be briquetted inside a cylindrical molding (17 mm diameter) and pressed under 100kg/cm2. The bio-briquettes are dried naturally at atmospheric temperature for 4 days before examined. The combustion performance and emission characteristics of each type of briquettes were investigated in a cylindrical combustion furnace equipped with measurement devices such as mass balance, thermocouple and exhaust gas analyzer. The burning rate and furnace temperature of each fuel composition were measured during the combustion process. An analysis was performed from the comparison of the data recorded in the form of graphs and tables. Emissions of the bio-briquettes combustion were examined using digital smoke analyzer, MEXA Analyzer, during the combustion process. The results of the study indicate that additional of the biomass carbonized into bio-briquettes offers the advantageous on combustion rate and emissions pollution. The rapid increase in the temperature in the combustion chamber was affected by the reaction rate between a fuel and oxygen as well as the size of fuel burned. The smaller the briquettes results in the faster the burning process and leads the higher the temperature in the combustion chamber.